2000
DOI: 10.1136/bjo.84.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Painful blind eye: efficacy of enucleation and evisceration in resolving ocular pain

Abstract: Aims-To assess the eVectiveness of enucleation or evisceration in relieving pain from painful blind eyes. Methods-24 patients with intractable ocular pain underwent enucleation or evisceration with or without an orbital implant. Results-Complete pain relief was achieved in all patients at an average time of 3 months (range 1-15 months). Seven patients required further medical or surgical treatment in addition to removal of the globe. Conclusion-Enucleation and evisceration were eVective in relieving ocular pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
2
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 3 publications
0
48
2
3
Order By: Relevance
“…Their study was based on an e-mail follow-up with 58 patients in 1999 (Custer & Reistad 2000). A retrospective study by Shah-Desai et al (2000) indicated that there was pain relief for all 24 patients treated with enucleation or evisceration.…”
Section: Identification Of Risks Factors For Developing Phantom Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study was based on an e-mail follow-up with 58 patients in 1999 (Custer & Reistad 2000). A retrospective study by Shah-Desai et al (2000) indicated that there was pain relief for all 24 patients treated with enucleation or evisceration.…”
Section: Identification Of Risks Factors For Developing Phantom Painmentioning
confidence: 99%
“…Possible aetiologies and treatments have been discussed in case reports (Glatt et al 1993;Waldman 1994;Kristinsson et al 1997). Specific causes of pain from the anophthalmic socket have been suggested: the need for modification or polishing of the prosthesis, conjunctival cysts, migration of the implant, lacrimal insufficiency, inflammatory or infectious conditions, tumours, haematoma, residual silicone band, amputation neurinomas, diseases of the brain and sinuses, compression or irritation of the trigeminal nerve and psychiatric causes (Glatt et al 1993;Shah-Desai et al 2000). Reflex sympathetic dystrophy has also been suggested as a cause for anophthalmic socket pain (Waldman 1994).…”
Section: Introductionmentioning
confidence: 99%
“…After the surgery, the mean VAS decreased to 2.88 with measuremanagement of ocular pain is complex and requires a multidisciplinary approach involving specialties such as anaesthesiology, ophthalmology, neurology and at times a specialized psychologist (7). Retrobulbar alcohol injection is a viable option for pain relief in patients who have cosmetically acceptable eyes as well as those who are either unwilling or unfit for more extensive surgery and subsequent management (8). Also, cyclocryotherapy provides good intraocular pressure control and good pain control.…”
Section: Resultsmentioning
confidence: 99%
“…[2] The injection of chemical neurolytic agents to the retrobulbar area is an alternative method for cases having a poor general health status for this surgery or having psychological, social, or religious reasons. [3,5] Alcohol injection to the retrobulbar area came up in the 1900s as an alternative method to enucleation. [21] It was thought to affect both coagulation in the nerve fibrils and damages that emerge with lipid precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Surgical removal of the eye is a prominent traditional treatment for resistant severe pain, if the level of vision is too poor. [4] However, the local application of some agents for neurolysis can be an alternative treatment if the patient has any psychological or medical concerns or enucleation or evisceration.…”
Section: Introductionmentioning
confidence: 99%